Role of innate immune cells in multiple sclerosis - Prado, Carolina; Herrada, Andrés A.; Hevia, Daniel; Goiry, Lorna Galleguillos; Escobedo, Noelia (Frontiers in Immunology, 2025)
Multiple sclerosis (MS) is a chronic autoimmune, inflammatory and neurodegenerative disease affecting the central nervous system (CNS). MS is associated with a complex interplay between neurodegenerative and inflammatory processes, mostly attributed to pathogenic T and B cells. However, a growing body of preclinical and clinical evidence indicates that innate immunity plays a crucial role in MS promotion and progression. Accordingly, preclinical and clinical studies targeting different innate immune cells to control MS are currently under study, highlighting the importance of innate immunity in this pathology. Here, we reviewed recent findings regarding the role played by innate immune cells in the pathogenesis of MS. Additionally, we discuss potential new treatments for MS based on targets against innate immune components.